Nowe modernizmy. Mapa debat - Cieślak-Sokołowski, Tomasz (Poznańskie Studia Polonistyczne. Seria Literacka, 2014)
The main task of the present article is the description of the contemporary discussions concerning the category of a literary modernism. Special attention is brought here to the debates conducted around the concept of periodization of literature of the 20th century and around those methodological approaches which privilege the new modernist studies. At the same time, the author of the article brings our attention to a special status of the contemporary modernist studies, which do not try to change the paradigm, but rather are organized by gestures of corrections and reconfiguration – thus they are subject to the mode of turns in the modern humanities.